The Influence of Organizational Factors on the Adoption of Energy Efficiency Measures in Companies - Vučković, Aleksandar; Džunić, Marija (Naše gospodarstvo/Our economy, 2023)
This paper aims to research the organizational factors influencing the implementation of energy efficiency measures in companies. The analysis was performed on a sample of companies from Serbia included in the World Bank Enterprise Survey. The raw data collected by the World Bank were utilized to analyze the correlation between various organizational factors and the adoption of energy efficiency measures. The analysis revealed a statistically significant correlation between management maturity and the implementation of energy efficiency measures in companies. These findings suggest that improving energy efficiency is not an isolated process but rather closely related to the maturity of management practices, highlighting the importance of comprehensive organizational development for achieving optimal energy management.